Impact Analysis of the Implementation of Sustainable Credit Governance and Corporate Social Responsibility (CSR) During the Covid-19 Pandemic at Bank X and Bank Y - Renny Kurniasari; Bachtiar Usman; Yosephina Endang Purba (International Journal Labs, 2023)
The increasing occurrence of non-performing loans can cause non-performing loans (NPL) loans to rise and have an impact on the Bank. Non-Performing Loan is the main parameter or ratio to measure the level of credit health in the banking sector, NPL consists of non-performing loans, so banks, especially the credit department, must be careful when realizing credit so that the credit is not problematic. This study aims to analyze the relationship between Bank X and Bank Y related to the implementation of credit governance and sustainable Corporate Social Responsibility (CSR) during the COVID-19 Pandemic at Bank X and Bank Y. Implementation of credit governance at Bank X and Bank Y is used as three pillars that are interconnected with Corporate Social Responsibility (CSR) related to credit loans during the COVID-19 era by developing the MSE Funding TJSL program. This is in line with the contribution of Bank X and Bank Y to Sustainable Economic Development (SDGs), namely in goal number 8 of Decent Work and Economic Growth. The implementation of ISO 26000 in organizational governance, fair operating practices, and consumer issues in both banks is well implemented. Sample the study by interviewing 14 respondents and using Content Analysis. The results showed that Bank X and Bank Y have implemented three ESG pillars as sustainable business efforts in Sustainable Banking, Sustainable Operation, and Sustainable Corporate Social Responsibility (CSR) during the COVID-19 pandemic. The two banks, namely Bank X and Bank Y have implemented sustainable business practices (Good) Corporate Governance & Sustainability Business in Banking). The existence of market risk, liquidity, legal risk and reputational risk, the strategic risk to both Banks does not affect the Bank in implementing sustainability practices.